Ответ:
В решении.
Объяснение:
Упростите выражение:
(a/(a - b) - a/(а + b)) ∶ а³/(a² - b²);
1) a/(a - b) - a/(а + b) =
= (а * (a + b) - a * (a - b))/(a + b)(a - b) =
= (a² + ab - a² + ab)/(a² - b²) =
= 2ab/(a² - b²);
2) 2ab/(a² - b²) : а³/(a² - b²) =
= (2ab * (a² - b²))/((a² - b²) * a³) =
= 2b/a².
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
В решении.
Объяснение:
Упростите выражение:
(a/(a - b) - a/(а + b)) ∶ а³/(a² - b²);
1) a/(a - b) - a/(а + b) =
= (а * (a + b) - a * (a - b))/(a + b)(a - b) =
= (a² + ab - a² + ab)/(a² - b²) =
= 2ab/(a² - b²);
2) 2ab/(a² - b²) : а³/(a² - b²) =
= (2ab * (a² - b²))/((a² - b²) * a³) =
= 2b/a².